Perceptions of what decolonisation means: An exploratory study amongst a sample of rural campus students - Chinyamurindi, W. T. (South African Journal of Higher Education, 2023)
There is growing interest within the South African academic press on understanding the issue of decolonisation from multiple viewpoints. Actuating these viewpoints are varying stakeholder interests. One such stakeholder within higher education being the student. The study explores student perceptions on the issue of decolonisation by using a sample of students at a rural campus in South Africa. The backdrop of the study comprises calls within the literature for nuanced understanding around the experience of decoloniality. The research utilised a focus group technique with 30 final year students enrolled within the Faculty of Management and Commerce. Narrative analysis using the three levels of meaning-making was used as the data analytical tool. The study revealed two main narratives. First, the negative concerns around decolonisation. This was informed by a lack of understanding of the concept. Second, students also expressed perceived opportunities that decolonisation has in changing the landscape of higher education in South Africa. Based on these findings, implications are made that affirm student experience as important. The study contributes to an ongoing discussion around aspects related to decolonisation. The focus of this work is on promoting voice around this topic and to provide suggestions for teaching practice.